The Architecture of the Self - Nagy-Szalóki, Zsuzsanna (Hungarian Journal of English and American Studies, 2021)
Book review:Ng, Andrew Hock Soon. Women and Domestic Space in Contemporary Gothic Narratives: The House as Subject. Basingstroke: Palgrave Macmillan, 2015. xiii + 246 pages. ISBN 978-1-137-53681-5. Hb. $90.